Beyond Bentham - Measuring Procedural Utility - Bruno S. Frey; Alois Stutzer (Center for Economic Studies and ifo Institute (CESifo), 2001)
We propose that outcome utility and process utility can be distinguished and empirically measured. People gain procedural utility from participating in the political decision-making process itself, irrespective of the outcome. Nationals enjoy both outcome and process utility, while foreigners are excluded from political decision-making and therefore cannot enjoy the corresponding procedural utility. Utility is measured by individuals' reported subjective well-being or happiness. We find that participation rights provide more procedural utility in terms of a feeling of self-determination and influence than actual participation.
Keywords: 330; Procedural utility; subjective well-being; political participation; participation rights